Intergranular Corrosion Rate Analysis of UNS N06625 Overlay Material Based on ASTM G28-2024 Testing - Adi Syahputra Purba; Mutia Amalia; Rona Cuana; Nur Fitria Pujo Leksonowati; Abdul Aziz Al Hakim Panjaitan (Universitas Medan Area, 2026)
Intergranular corrosion is one of the degradation mechanisms that can reduce the reliability of nickel-based alloy materials in corrosive environments. UNS N06625 is well known for its excellent corrosion resistance due to the presence of alloying elements such as chromium, nickel, and molybdenum, which promote the formation of a stable passive layer. This study aims to determine the intergranular corrosion rate of UNS N06625 overlay material based on the ASTM G28-2024 Method A testing standard. Corrosion testing was conducted by immersing specimens in a corrosive solution at boiling temperature for 120 hours, and the corrosion rate was calculated using the mass loss method. The results indicate an intergranular corrosion rate of 0.454 mm/year, demonstrating excellent corrosion resistance. The low corrosion rate is associated with the stability of the microstructure and the effectiveness of the passive oxide layer in inhibiting corrosion processes. Therefore, UNS N06625 overlay material is considered suitable for applications in highly corrosive environments.